Genetic and environmental variation of seed weight in Trichloris species (Chloridoideae, Poaceae) and its association with seedling stress tolerance - Marinoni, Lorena del Rosario (2018)
Background: Seed weight is a key fitness-related trait associated with plant adaptation and is commonly targeted in plantbreeding.Aims: We evaluated seed weight variation within and between Trichloris crinita and Trichloris pluriflora across theirgeographical ranges in Argentina.Methods: Genetic variation in seed weight was evaluated through a common garden experiment. To examine the possiblerole of such variation in local adaptation, we compared the seed weight of plants of populations raised in the commongarden with seed weight variation and ecogeographical variables across their original habitats. We also evaluatedexperimentally the effects of seed weight variation upon osmotic stress tolerance at germination.Results: Variation in seed weight existed in both species. Such variation had a genetic basis in T. crinita related to severalecogeographical variables. Larger seeds of T. crinita were associated with more stressful environments and producedlarger seedlings under both osmotic stress and non-stress conditions.Conclusions: Our results suggest that seed weight variation in T. crinita is likely adaptive, with large seed having anadvantage during early developmental stages, particularly under stressful conditions. Such knowledge should prove helpfulin selecting the most suitable populations for restoration and plant breeding.